A holistic approach to ship design. Volume 2, - Papanikolaou, Apostolos (Springer, 2021)
This book deals with modern Computer-Aided Design (CAD) software tools and platforms implemented in ship design, the integration of techno-economic databases, the use of optimisation and simulation software tools, which are integrated in these platforms, and the virtual modelling of ships and their operation by using a Virtual Vessel Framework (VVF). It contains a series of application case studies related to the developed holistic approach to ship design and operation. Nine case studies are described, referring to the design and operation of various ship types, namely RoPax, cruise ship, double-ended ferry, bulk carrier, containership, offshore support vessel, ocean surveillance ship and research vessel and one offshore structure. All case studies are driven by leading representatives of the European Maritime Industry. This book complements A Holistic Approach to Ship Design, volume 1, which covers methods and tools for the life cycle optimisation and assessment of ship design and operation.